2020
DOI: 10.1126/sciadv.aaz8521
|View full text |Cite
|
Sign up to set email alerts
|

Efficient blockade of locally reciprocated tumor-macrophage signaling using a TAM-avid nanotherapy

Abstract: Interpreting how multicellular interactions in the tumor affect resistance pathways to BRAF and MEK1/2 MAPK inhibitors (MAPKi) remains a challenge. To investigate this, we profiled global ligand-receptor interactions among tumor and stromal/immune cells from biopsies of MAPK-driven disease. MAPKi increased tumor-associated macrophages (TAMs) in some patients, which correlated with poor clinical response, and MAPKi coamplified bidirectional tumor-TAM signaling via receptor tyrosine kinases (RTKs) including AXL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…For track-based analyses sample sizes were not predetermined as all the tracks computationally determined were used for downstream analyses. Sample sizes for cells, tumors, or mice were chosen based on estimated effect sizes from prior studies with this xenograft model and in vitro cell culture experiments 19 , 20 , 23 , 24 , 64 . All experiments were performed with ≥2 independent replicates as described in the figure captions.…”
Section: Methodsmentioning
confidence: 99%
“…For track-based analyses sample sizes were not predetermined as all the tracks computationally determined were used for downstream analyses. Sample sizes for cells, tumors, or mice were chosen based on estimated effect sizes from prior studies with this xenograft model and in vitro cell culture experiments 19 , 20 , 23 , 24 , 64 . All experiments were performed with ≥2 independent replicates as described in the figure captions.…”
Section: Methodsmentioning
confidence: 99%
“…Past clinical trials, including one that studied a small cohort of melanoma patients, have found correlation between MΦ infiltration and poor response to immune checkpoint blockade using the programmed death 1 (PD1) targeted monoclonal antibody (mAb) nivolumab [10]. Additionally, in a small study of 9 patients with melanoma, kinase inhibitor response correlated more negatively with the drug-induced accumulation of MΦ than any other immune cell-type assessed [11]. These instances of clinical correlations and many others suggest that MΦ quantification may be useful in predicting responses to a variety of different drugs [12].…”
Section: Ivyspringmentioning
confidence: 99%
“…IgG4, deglycosylated mAbs, Fc-null or Fc-effectorless mAbs) act instead to bind and block extracellular signal transmission [79]. FcγR2b is unique in that it has an ITIM (immunoreceptor tyrosine-based inhibition motif) domain in place of the activating ITAM (immunoreceptor tyrosine-based [11] using scRNAseq data GSE72056 [28], copyright 2020. B) Average expression values corresponding to single-cell data in A.…”
Section: Pathways Of Receptor-mediated Uptakementioning
confidence: 99%
See 2 more Smart Citations